Evaluating the Impact of E-Service Quality Attributes on Customer Satisfaction and Purchase Intentions for Electronic Gadgets and Home Appliances, India - Reddy, N.Nagasubba; Ramaprasad, M V; M, Jahnavi; Bung, Purushottam (Journal of Ecohumanism, 2024)
The objective of the study is to analyse the impact of e-service quality attributes on customer satisfaction and on purchase intention and purchase frequency of electronic gadgets and home appliances in Bangalore, India using the service quality (SERVQUAL) model. The e-service quality attributes chosen for the study are empathy, information, security, reliability, user interface, responsiveness, fulfillment, and personalization. This paper extends existing research by quantifying the impact of chosen attributes of e-service quality on customer satisfaction and purchase intentions, and on purchase frequency. 120 responses were collected for the analysis through an online questionnaire using convenience sampling. A diverse mix of respondents who are proficient in digital platform navigation and online purchases were chosen for the study. SPSS and R studio was applied to analyze the data. The techniques used for the study to test the hypothesis and to understand the relationship between the e-service quality attributes on customer satisfaction and purchase intention are descriptive statistics, chi-square, correlation, logistic regression, decision tree, SEM, and k-fold cross-validation. The results indicate that personalization, and fulfillment have a significant impact on customer purchase intention, the attributes fulfillment and information are key attributes for purchase frequency. From SEM analysis it is evident that all the chosen e-service quality attributes have a positive impact on customer satisfaction and it is significant, which in turn enhances purchase intention and purchase frequency. From decision tree analysis it is evident that customers aged 20-40 prefer buying products after verifying seller information on shopping websites. The results of the study provide valuable insights into the e-commerce sector to make better policies and strategies to enhance customer satisfaction and purchase intention.